Dynamic monitoring of neutrophil/lymphocyte ratio, APACHE II score, and SOFA score predict prognosis and drug resistance in patients with Acinetobacter baumannii–calcoaceticus complex bloodstream infection: a single-center retrospective study - Wei, Zhiyong; Zhao, Lina; Yan, Jia; Wang, Xuejie; Li, Qun; Ji, Yuanyuan; Liu, Jie; Cui, Yan; Xie, Keliang (Frontiers in Microbiology, 2024)
Objective ： To evaluate the clinical value of dynamic monitoring of neutrophil/lymphocyte ratio (NLR), APACHE II(Acute Physiology and Chronic Health Evaluation II) score and SOFA (Sequential Organ Failure Assessment)score in predicting 28-day prognosis and drug resistance in patients with bloodstream infection with Acinetobacter baumannii-calcoaceticus complex(Abc complex). Patients and methods: In this research, individuals admitted to Tianjin Medical University General Hospital from January 2017 to March 2023 with bloodstream infections and a minimum of one Abc complex positive blood culture were chosen. The risk factors for 28-day prognosis and drug resistance were analyzed using logistic regression. The NLR, APACHE II score, and SOFA score were evaluated for predicting 28-day prognosis and drug resistance using a ROC curve analysis. The data was analyzed using R Studio to find correlations and conduct survival analysis with the Kaplan-Meier method. Results: The final statistical analysis included a total of 129 patients with bloodstream infections caused by Abc complex. Independent risk factors predicting mortality within 28 days were identified as follows: the SOFA score and APACHE II scores at 24 hours, and APACHE II scores at 72 hours after the onset of blood infection (P < 0.05). NLR, SOFA score, and APACHE II score did not predict drug resistance. Patients with Carbapenem-resistant Acinetobacter baumannii-calcoaceticus complex ( CRAB ) had shorter survival times compared to those with carbapenem-sensitive strains (40.77 d vs 47.65 d respectively, P=0.0032). Conclusion: The prognosis of Abc complex bloodstream infection is affected by both SOFA and APACHE II scores. Both scoring systems have similar prognostic value at different time points after infection, but for computational convenience, it is recommended to use the SOFA score. NLR exhibits limited effectiveness in predicting mortality within 28 days. Carbapenem-resistant individuals with Abc complex experience significantly reduced survival time. None of the three factors -SOFA score, APACHE II score, and NLR -can early predict the occurrence of CRAB infections effectively.